Archaeology and Bioarchaeology of Anatomical Dissection at a Nineteenth-Century Army Hospital in San Francisco - Milligan, Colleen F.; Bartelink, Eric J.; Gavette, Peter; Willey, Patrick S. (Book collections on Project MUSE., 2023)
"An archaeological site that tells a story of structural violence in medical researchIn 2010, a pit containing over 4,000 human skeletal elements was discovered at the site of the former Army hospital at Point San Jose in San Francisco. Local archaeologists determined that the bones, which were found alongside medical waste artifacts from the hospital, were remains from anatomical dissections conducted in the 1870s. As no records of these dissections exist, this volume turns to historical, archaeological, and bioarchaeological analysis to understand the function of the pit and the identities of the people represented in it. In these essays, contributors show how the remains discovered are postmortem manifestations of social inequality, evidence that nineteenth-century surgical and anatomical research benefited from and perpetuated structural violence against marginalized individuals. A volume in the series Bioarchaeological Interpretations of the Human Past: Local, Regional, and Global Perspectives, edited by Clark Spencer Larsen"--